Regulation of protein abundance in genetically diverse mouse populations - Gregory R. Keele; Tian Zhang; Duy T. Pham; Matthew Vincent; Timothy A. Bell; Pablo Hock; Ginger D. Shaw; Joao A. Paulo; Steven C. Munger; Fernando Pardo-Manuel de Villena; Martin T. Ferris; Steven P. Gygi; et al. (Elsevier, 2021)
Summary: Genetically diverse mouse populations are powerful tools for characterizing the regulation of the proteome and its relationship to whole-organism phenotypes. We used mass spectrometry to profile and quantify the abundance of 6,798 proteins in liver tissue from mice of both sexes across 58 Collaborative Cross (CC) inbred strains. We previously collected liver proteomics data from the related Diversity Outbred (DO) mice and their founder strains. We show concordance across the proteomics datasets despite being generated from separate experiments, allowing comparative analysis. We map protein abundance quantitative trait loci (pQTLs), identifying 1,087 local and 285 distal in the CC mice and 1,706 local and 414 distal in the DO mice. We find that regulatory effects on individual proteins are conserved across the mouse populations, in particular for local genetic variation and sex differences. In comparison, proteins that form complexes are often co-regulated, displaying varying genetic architectures, and overall show lower heritability and map fewer pQTLs. We have made this resource publicly available to enable quantitative analyses of the regulation of the proteome.